Desafios da acess\~ao da Rússia à OMC - Vera Thorstensen; Carolina Müller; Daniel Ramos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This study aims to analyze the commitments undertaken by Russia at the moment of its accession to the World Trade Organization (WTO), in order to evaluate the impacts that these may have on the multilateral trading system. Russia was the last main economy outside the WTO. In order to allow its accession to the organization, WTO members demanded a series of commitments that would grant them a larger access to the Russian market and would assure that the country would adapt its economic system to the rules of the multilateral trading system. The country undertook obligations related to the oil and gas sector, state presence in the economy, subsidy programs and enforcement of intellectual property rules. Basedon the analysis of such commitments and comparing them with China's accession to the WTO, in 2001, the article shall identify the main features of Russian economy that may present a challenge to its full participation in the multilateral trading system.
Keywords: F10; F13; F50; 330; WTO; accession; Russia; international trade